Self-efficacy Relationship With Social Health among Nurses in Taleghani Hospital in Kermanshah - Ayoub Mohammadi; Parvaneh Kheftan; Borzoo Amirpour; Maryam Alsadat Sepidehdam; Fatemeh Gholami Jam (Iranian Association of Health Education and Health Promotion, 2018)
Background and objective: Health is a multi-dimensional concept, and the WHO has pointed to its four physical, psychological, spiritual and social dimensions. Social health is one of the most important health indicators of each country and can be influenced by different factors. The purpose of this study was to investigate the relationship between self-efficacy and social dimensions of nurses. Methods: The research method was descriptive-analytic, correlation type. The statistical population was nurses working in Taleghani Hospital in Kermanshah in 2016 . A sample of 100 were selected using randomized sampling method. Data were collected using the Key Health Social Questionnaire and Sherer Self-efficacy Questionnaire. Data were entered into SPSS-22 software and analyzed using Pearson correlation, independent t-test and one-way ANOVA. Results: The results showed that there was a significant relationship between nurses' self-efficacy and their social health (p <0.05). Also, there was no significant relationship between self-efficacy with demographic variables such as age, sex, education, residence and income level (p> 0.05). Conclusion: This research shows that there is a meaningful relationship between self-efficacy of the population studied and their social health. However, through self-efficacy-based interventions and education, the nurses' social health status was promoted.